# Example 12 - Chapter 8 Class 11 Binomial Theorem

Last updated at Sept. 3, 2021 by Teachoo

Examples

Example 1

Example 2 Important

Example 3 Important

Example 4

Example 5 Important Deleted for CBSE Board 2023 Exams

Example 6 Important Deleted for CBSE Board 2023 Exams

Example 7 Deleted for CBSE Board 2023 Exams

Example 8 Important Deleted for CBSE Board 2023 Exams

Example 9 Deleted for CBSE Board 2023 Exams

Example 10 Important Deleted for CBSE Board 2023 Exams

Example 11 Important Deleted for CBSE Board 2023 Exams

Example 12 Deleted for CBSE Board 2023 Exams You are here

Example 13 Important Deleted for CBSE Board 2023 Exams

Example 14 Important Deleted for CBSE Board 2023 Exams

Example 15 Important Deleted for CBSE Board 2023 Exams

Example 16 Deleted for CBSE Board 2023 Exams

Example 17 Important Deleted for CBSE Board 2023 Exams

Last updated at Sept. 3, 2021 by Teachoo

Example 12 Show that the coefficient of the middle term in the expansion of (1 + x)2n is equal to the sum of the coefficients of two middle terms in the expansion of (1 + x)2n – 1. Middle term of (1 + x)2n Since 2n is even, Middle term = (2n/2 " +1" )^𝑡ℎ = ("n + 1")th term = Tn+1 We know that general term of expansion (a + b)n is Tr + 1 = nCr an – r br For (1 + x)2n , r = n , n = 2n , a = 1 , b = x Putting values Tn+1 = 2nCn (1)2n–n . (x)n Tn+1 = 2nCn.(x)n Hence, Coefficient is 2nCn Middle term of (1 + x)2n – 1 Since 2n – 1 is odd, There will be 2 middle terms ((2n − 1) + 1)/2 and (((2n − 1) + 1)/2 " + 1" ) term = nth term and (n + 1)th terms. = Tn and Tn+1 We know that general term for expansion (a + b)n Tr+1 = n Cr an–r br For Tn in (1 + x)2n – 1 Putting r = n – 1 , n = 2n – 1 , a = 1 & b = x Tn – 1 + 1 = 2n – 1Cn – 1 . (1) (2n – 1) – (n–1) .x n – 1 Tn = 2n – 1Cn – 1 .(x)n – 1 Hence, coefficient is 2n – 1Cn – 1 Similarly, For Tn + 1 in (1 + x)2n – 1 Putting r = n , n = 2n – 1 , a = 1 & b = x Tn+1 = 2n – 1Cn . (1)2n – 1 – n . xn = 2n–1Cn . xn Hence, Coefficient is 2n–1Cn Now we have to prove Coefficient of middle term of (1+x)2n = Sum of coefficient of middle term of (1 + x)2n–1 2nCn = 2n – 1Cn – 1 + 2n – 1Cn Thus, We have to prove 2nCn = 2n – 1Cn – 1 + 2n – 1Cn 2nCn = 2𝑛!/𝑛!(2𝑛 − 𝑛)! = 2𝑛!/(𝑛!(𝑛)!) 2n – 1Cn – 1 + 2n – 1Cn = ((2𝑛 − 1)!)/((𝑛 − 1) ![(2𝑛 −1) − (𝑛 − 1)]!) + (2𝑛 − 1)!/(𝑛! (2𝑛 − 1 − 𝑛)!) = ((2𝑛 − 1)!)/((𝑛 − 1) !(2𝑛 − 1 − 𝑛 + 1)!) + (2𝑛 −1)!/(𝑛! (2𝑛 −1 − 𝑛)!) = ((2𝑛 − 1)!)/((𝑛 −1)! (𝑛)!) + (2𝑛 − 1)!/(𝑛! (𝑛 −1)!) = 2 × ((2𝑛 − 1)!)/(𝑛! (𝑛 − 1)! ) = 2 × ((2𝑛 − 1)!)/(𝑛! (𝑛 − 1)! ) × 𝑛/𝑛 = (2𝑛(2𝑛 − 1)!)/(𝑛!𝑛(𝑛 − 1)! ) = 2𝑛!/(𝑛! 𝑛! ) = L.H.S Hence L.H.S = R.H.S Hence proved